Association between Inspirational Leadership Traits and Job Commitment among Secondary School Teachers in a Remote District of Uganda - Akurut, Christine Rose; Rukundo, Aloysius (Canadian Journal of Educational and Social Studies, 2021)
Aim: Establishing the association between the dimensions of perceived inspirational leadership traits and job commitment among secondary school teachers. Methods: It was cross-sectional, with quantitative approach. A questionnaire was used to obtain data from 250 teachers. Linear regressions in SPSS were used to determine the association between study variables. Results: Combined commitment was significantly associated with flexibility and listening, but not with responsibility. After separation of the commitment dimensions, normative commitment was associated with flexibility, listening, and responsibility. However affective commitment was associated with flexibility and listening, while continuance commitment was associated with only flexibility. All the three leadership traits accounted for 21.7% of the variance in combined commitment. Conclusion: Inspirational leadership is crucial in normative commitment of teachers towards their job. Further, leadership traits could serve to motivate teachers to engage in activities, beyond the job requirements, in a way that makes them perform better in their obligations.
Keywords: Leadership Traits; Inspiration; Commitment; Teachers; Secondary Schools; Uganda